The Viability of Single Cancer Cells after Exposure to Hydrodynamic Shear Stresses in a Spiral Microchannel: A Canine Cutaneous Mast Cell Tumor Model - Ketpun, Dettachai (2018)
Our laboratory has the fundamental responsibility to study cancer stem cells (CSC) in various models of human and animal neoplasms. However, the major impediments that spike our accomplishment are the lack of universal biomarkers and cellular heterogeneity. To cope with these restrictions, we have tried to apply the concept of single cell analysis, which has hitherto been recommended throughout the world as an imperative solution pack for resolving such dilemmas. Accordingly, our first step was to utilize a predesigned spiral microchannel fabricated by our laboratory to perform size-based single cell separation using mast cell tumor (MCT) cells as a model. However, the impact of hydrodynamic shear stresses (HSS) on mechanical cell injury and viability in a spiral microchannel has not been fully investigated so far. Intuitively, our computational fluid dynamics (CFD) simulation has strongly revealed the formations of fluid shear stress (FSS) and extensional fluid stress (EFS) in the sorting system. The panel of biomedical assays has also disclosed cell degeneration and necrosis in the model. Therefore, we have herein reported the combinatorically detrimental effect of FSS and EFS on the viability of MCT cells after sorting in our spiral microchannel, with discussion on the possibly pathogenic mechanisms of HSS-induced cell injury in the study model.